Percutaneous Coronary Intervention of Complex Calcified Lesions With Drug‐Coated Balloon After Rotational Atherectomy. (23rd January 2017) - Rissanen, Tuomas T.; Uskela, Sanna; Siljander, Antti; Kärkkäinen, Jussi M.; Mäntylä, Pirjo; Mustonen, Juha; Eränen, Jaakko
Abstract : Objectives: We investigated the safety and efficacy of PCI using drug‐coated balloon (DCB) after rotational atherectomy (rotablation) in a retrospective single center study in patients with calcified de novo coronary lesions. The majority of patients had an increased risk for bleeding. Background: DCB has been effective in the treatment of in‐stent restenosis, small vessels, and bifurcations. DCB enables short one month dual antiplatelet treatment. No published data exist on the use of DCB after rotablation. Methods: 82 PCIs were performed in 65 patients (mean age 72 ± 10 years) using rotablation followed by DCB treatment. The median follow‐up time was 17 months. 82% of the patients had at least one risk factor for bleeding such as oral anticoagulation. 32% had an acute coronary syndrome. Median duration of dual antiplatelet treatment was 1 month. Results: MACE (the composite of cardiovascular death, ischemia‐driven target‐lesion revascularization [TLR] or non‐fatal myocardial infarction) occurred in 14% and 20% of the patients at 12 and 24 months, respectively. The rate of ischemia‐driven TLR was 1.5% at 12 months and 3.0% at 24 months. No acute closure of the treated vessel occurred. Bailout stenting was needed in 10% of the PCIs. The incidence of significant bleeding was 9% at 12 months. Conclusions: This is the first study to show that PCI using DCB after preparation of calcified lesions with rotablation is safe and effective. This novel strategy may be considered especially in patients with a bleeding risk such as those using an oral anticoagulant.